The molecular genetics of the risk factors of vascular dementias* - Hentschel, Frank; Kölsch, Heike (Clinical neuroradiology, 2007)
Secondary prevention of the age-associated dementias requires clarification of the risk factors. Vascular dementia is mainly due to cerebral hypoxic or hemorrhagic infarcts as a consequence of cerebrovascular disease. For this reason attention must be paid to the risk factors of cerebrovascular diseases. Both environmental and genetic causes determine the manifestation of these risk factors, for example, factors related to cholesterol and glucose metabolism, regulation of blood pressure and inflammatory cascades. Disturbances of genetically driven processes increase the risk of a cerebrovascular event. In this respect candidate genes and their polymorphisms need to be considered.
Gesehen am 19.10.2020